Verkiezing Jonge Socialisten bestuur. Zittend achter de rij: Van Hooft. V.l.n.r. : Koopman, De Koning, ?, Benders, Leerink, Wallenaar, Wijfje, Faber, Veldt, Groene, Zonneveld (1985)
Verkiezing Jonge Socialisten bestuur. Zittend achter de rij: Van Hooft. V.l.n.r. : Koopman, De Koning, ?, Benders, Leerink, Wallenaar, Wijfje, Faber, Veldt, Groene, Zonneveld.